2011
DOI: 10.1002/ptr.3559
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 12‐week Oral Supplementation of Ecklonia cava Polyphenols on Anthropometric and Blood Lipid Parameters in Overweight Korean Individuals: A Double‐blind Randomized Clinical Trial

Abstract: The effects of 12-week supplementation with a polyphenol extract from Ecklonia cava (ECP) on anthropometry, serum biochemistry and hematology have been investigated. Ninety-seven overweight male and female adults (average age 40.5 ± 9.2 yr and body mass index (BMI) of 26.5 ± 1.6 kg/m²) were enrolled in a randomized, double-blind, placebo-controlled trial with parallel-group design. Subjects were randomly allocated into three groups designated as PC (placebo), LD (low-dose, 72 mg-ECP/day) and HD (high-dose, 144… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 27 publications
3
86
1
Order By: Relevance
“…Yeo et al (2012) also reported both polyphenols and dieckols isolated from EC did not increase serum HDL-cholesterol levels but significantly lowered total-cholesterol, LDL-cholesterol and triglyceride levels in High-Fat Diet (HFD)-fed mice. On the other hand, according to the other studies mentioned above, both extracts from EC (Shin et al, 2012) and ES (Yoon et al, 2008) not only increased HDL-cholesterol levels but also lowered total and LDL-cholesterol levels.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Yeo et al (2012) also reported both polyphenols and dieckols isolated from EC did not increase serum HDL-cholesterol levels but significantly lowered total-cholesterol, LDL-cholesterol and triglyceride levels in High-Fat Diet (HFD)-fed mice. On the other hand, according to the other studies mentioned above, both extracts from EC (Shin et al, 2012) and ES (Yoon et al, 2008) not only increased HDL-cholesterol levels but also lowered total and LDL-cholesterol levels.…”
Section: Discussionmentioning
confidence: 53%
“…Shin et al (2012) reported that polyphenols extracted from EC decreased total cholesterol by 9.2% and LDL-cholesterol by 14.2% in overweight human subjects (Shin et al, 2012). The reduction of 2.8% in total cholesterol and the 11.1% for LDL-cholesterol at 12 weeks, obtained with 400 mg dayG 1 of ECE in this study were lower than those obtained by Shin et al (2012) at a dosage of 144 mg dayG 1 from a similar baseline levels, which can be attributed to the different test products used and highlights the need to express the concentration of active substances of these extracts according to quality standards. Yoon et al (2008) reported that extract of Ecklonia stolonifera (ES) and its phlorotannin constituents, eckols and dieckols, reduced total and LDL-cholesterol levels in hyperlipidemic rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are partially consistent with findings of the present study. In another 12-week RCT among overweight Korean adults [30], a polyphenol extract from Ecklonia cava significantly contributed to lowering body fat and serum lipid parameters such as total and LDL cholesterols with dose dependence. It also had some BP-lowering effects, although its doseresponse effect was not significant.…”
Section: Discussionmentioning
confidence: 98%